Lichens of Ireland : an illustrated introduction to over 250 species - Whelan, Paul (Doughcloyne, Wilton, Cork : The Collins Press, 2011)
This is a stimulating guide to over 200 Irish lichens. The book features colour photographs and maps to aid identification. Each description includes appropriate spot test results, spore size, and notes on the habitat/substrate that the lichen is most likely to occupy, and much more
Includes bibliographical references (pages 152-153) and index
Keywords: Lichens -- Ireland -- Identification; Lichens -- Ireland -- Pictorial works